PENGARUH IMPLEMENTASI KONSEP TRI KAYA PARISUDHA TERHADAP KINERJA KEUANGAN LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN BADUNG: The Influence Of The Implementation Of The Tri Kaya Parisudha Concept On The Financial Performance Of Village Credit Institutions (LPD) In Badung Regency - Artini, Rai; Pynatih, Ngurah Made Novianha (Ganec Swara, 2025)
This study aims to determine the effect of Tri Kaya Parisudha (manacika, wacika, and kayika) on the financial performance of LPDs in Badung Regency. The research was conducted on LPDs in Badung Regency. The objects of this study are manacika, wacika, kayika, and the financial performance of LPDs in Badung Regency. The total sample in this study consisted of 55 respondents, selected using proportional random sampling. The data analysis technique used is Multiple Linear Regression Analysis. The results of this study indicate that all independent variables (manacika, wacika, and kayika) have a partial, positive, and significant effect on the financial performance of LPDs in Badung Regency. The simultaneous implementation of Tri Kaya Parisudha (manacika, wacika, and kayika) also has a significant effect on the financial performance of LPDs in Badung Regency